Clinical Features and Management of Some Muscular Disorders in Children - A Brief Review - Dwi Putro Widodo (Paediatrica Indonesiana, 1998)
Study has proven that electrical activity of resting and contracting skeletal muscles and conduction of the nerve impulse have become one of the most useful diagnostic tools in neurology. EMG and nerve conduction studies have become indispensable in the diagnosis and management of peripheral nerve and muscle disease (neurological differential diagnosis).